UX : tales from the trenches. (SitePoint, 2019)
This book is a collection of hard-won lessons from UX experts, gained from many years of working in the field. It contains: How Analytics Helped Solve a UX Issue by Luke Hay Using Prototyping Tools to Define Better Weather Icons for Everyone by Dan Goodwin How User Research Turned a Good App into a Great One by Jodie Moule Accessibility and Inclusive Design: Why They're Not the Same by Derek Featherstone Exposing the Real Cause of Most UX Issues by Joe Natoli.